2014
DOI: 10.56431/p-1qr397
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition and Fatty Acid Analysis of Puffer Fish, <i>Lagocephalus inermis</i> (Temminck and Schlegel, 1850) and <i>Lagocephalus lunaris</i> (Bloch and Schneider, 1801) from Parangipettai, Southeast Coast of India

Abstract: The nutritional effects of marine food have increased far and wide due to the beneficial effects of consuming marine food, fats and oils. In general, the proximate composition is well known as a proportion composition of basic elements such as protein, lipids, carbohydrate, minerals and water. The puffer fish Lagocephalus lunaris and Lagocephalus inermis were collected at Mudasal odai fish landing centre and the skin and visceral organs like gonads and intestines were removed the edible portion only took for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…So, a low flow rate of 1 m/s was selected to simulate the flow field around the pufferfish because it is a low-speed swimming fish. 40,41 This flow rate is deemed appropriate for observing and analyzing their swimming behavior and dynamics in conditions closely resembling their natural environment. The corresponding turbulence intensity was 3.26% and the turbulence viscosity ratio was 4.15, with the pressure outlet serving as the outlet boundary condition.…”
Section: ■ Experiments and Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, a low flow rate of 1 m/s was selected to simulate the flow field around the pufferfish because it is a low-speed swimming fish. 40,41 This flow rate is deemed appropriate for observing and analyzing their swimming behavior and dynamics in conditions closely resembling their natural environment. The corresponding turbulence intensity was 3.26% and the turbulence viscosity ratio was 4.15, with the pressure outlet serving as the outlet boundary condition.…”
Section: ■ Experiments and Simulationsmentioning
confidence: 99%
“…Drucker and Lauder and Tytell demonstrated that the use of particle image velocimetry at low flow velocities allows better quantification of the three-dimensional vortex structure around the fish body and modeling of fish dynamics compared to high flow velocities. So, a low flow rate of 1 m/s was selected to simulate the flow field around the pufferfish because it is a low-speed swimming fish. , This flow rate is deemed appropriate for observing and analyzing their swimming behavior and dynamics in conditions closely resembling their natural environment. The corresponding turbulence intensity was 3.26% and the turbulence viscosity ratio was 4.15, with the pressure outlet serving as the outlet boundary condition.…”
Section: Experiments and Simulationsmentioning
confidence: 99%